Akuntansi Program Pensiun Berdasarkan PSAK 18: Studi Kasus pada PT Antam Perwakilan Makassar - Fitriyanti Nur; Andi Sri Wahyuni (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2022)
The purpose of this study is to describe and compare the accounting procedures and treatments for the Pension Program applied by PT Antam with PSAK 18 of 2015. The research method used by the author is descriptive data analysis method, namely collecting data, classifying, processing and analyzing data in order to obtain an overview of the problem. researched, then provide suggestions on the basis of conclusions. The type of data collected is qualitative data consisting of primary data and secondary data. In this study, the nature of the research used is a case study. With this method, obtained facts about the procedures and accounting treatment of pension plans by observing and analyzing a problem object of research that occurs in a research location on the existing suitability and then draw conclusions from the problems studied. After conducting research, judging from the regulations applied, the formula used, and the financial reporting, the authors obtained the results that the accounting procedures and treatment for the pension program at this company were in accordance with PSAK 18. This research is important for the company concerned and similar companies in Indonesia. to be a reference material and the basis for further performance improvement related to the company's pension program.